Distribution, activity patterns and diet of Callithrix penicillata (Primates: Callithrichidae) in an urban area in central Brazil (Research, Society and Development, 2022)
Urban remnants have been home to large groups of marmosets. However, ecological information about black-tufted marmosets, Callithrix penicillata (É. Geoffroy Saint-Hilaire, 1812) on urban areas are scant in the scientific literature. Here, we investigated the distribution, interaction with residents, activity pattern and diet of C. penicillata in an urban area in central Brazil. We used direct observation (sightings and scan sampling) and 205 semi-structured interviews to evaluate distribution, interaction and ecological behavior of black-tufted marmosets. Callithrix penicillata occurred throughout the urban area of Quirinópolis municipality, occupying mainly the forest remnants and surrounding gallery forests. Supplementary feeding was the interaction most cited by people. However, C. penicillata spend most of their time in locomotion (35-40%) and resting (30%), and exudates and supplementary foods represented a large part of their diet. We conclude that C. penicillata are well adapted in urban area of central Brazil. However, due interaction with people, we highlighted that these marmoset populations should be part of future municipal public policy concern.